The Catalyst to Activate Rural Economic Vitality: The Impact of Land Transfer on the Consumption Behaviour of Older Farmers in China - Peng Cheng; Qiaosen Jin; Yunhua Xiang (Land)
Against the backdrop of the current rural economic transformation and the intensification of the ageing process, land transfer, as an important land policy tool, has gradually become a key factor influencing the consumption behaviour of farmers, especially older farmers. Based on the four-period panel data of the China Family Panel Studies (CFPS), this study uses a two-way fixed-effects model to examine the impact of land transfer (land transfer-out, land transfer-in, and two-way land transfer) on the consumption behaviour of older farmers. This study finds that land transfer-out significantly increases the total consumption of older farmers and promotes subsistence, healthy, and hedonic consumption. In contrast, land transfer-in does not show a significant effect on hedonic consumption. The mechanism test reveals that household income plays a key mediating role in the process of land transfer, affecting the consumption behaviour of older farmers. Two-way land transfer promotes the consumption level and the upgrading of the consumption structure of older farmers through income portfolio optimisation and risk diversification.